A 1995 Social Accounting Matrix (SAM) for Indonesia - International Food Policy Research Institute (International Food Policy Research Institute, 2003)
The 1995 SAM for Indonesia is a 57x57 matrix with accounts for 17 sectors (separate activities and commodities), 6 factors, 7 households, 1 enterprise, the government, the rest-of-the-world, 2 tax types, and aggregate institutional savings-investments. The SAM is an aggregation of a 22 sector SAM produced by the Indonesia statistical authority with a revised treatment of trade and transportation costs (disaggregation across imports, exports and domestic sales on the basis of value shares). For a description of the construction and use of this SAM, download the Trade and Macroeconomics Division Discussion Paper Number 42: (PDF 149K)